Review on High‐Loading and High‐Energy Lithium–Sulfur Batteries - Peng, Hong‐Jie; Huang, Jia‐Qi; Cheng, Xin‐Bing; Zhang, Qiang (Advanced energy materials, 2017)
Owing to high specific energy, low cost, and environmental friendliness, lithium–sulfur (Li–S) batteries hold great promise to meet the increasing demand for advanced energy storage beyond portable electronics, and to mitigate environmental problems. However, the application of Li–S batteries is challenged by several obstacles, including their short life and low sulfur utilization, which become more serious when sulfur loading is increased to the practically accepted level above 3–5 mg cm−2. More and more efforts have been made recently to overcome the barriers toward commercially viable Li–S batteries with a high sulfur loading. This review highlights the recent progress in high‐sulfur‐loading Li–S batteries enabled by hierarchical design principles at multiscale. Particularly, basic insights into the interfacial reactions, strategies for mesoscale assembly, unique architectures, and configurational innovation in the cathode, anode, and separator are under specific concerns. Hierarchy in the multiscale design is proposed to guide the future development of high‐sulfur‐loading Li–S batteries. High‐sulfur‐loading lithium–sulfur (Li–S) batteries enabled by multiscale hierarchical design principles are reviewed. The basic insights into the interfacial reactions, strategies for mesoscale assembly, unique architectures, and configurational innovation in the cathode, anode, and separator are of specific concern. Hierarchy in the multiscale design is proposed to guide the future development of high‐sulfur‐loading Li–S batteries.